2006
DOI: 10.3189/172756406781812168
|View full text |Cite
|
Sign up to set email alerts
|

Glacier retreat as a result of climate warming and increased precipitation in the Tarim river basin, northwest China

Abstract: ABSTRACT. The Tarim river basin, a river system formed by the convergence of nine tributaries, is the most heavily glacierized watershed in arid northwest China. In the basin, there are 11 665 glaciers with a total area of 19 878 km 2 and a volume of 2313 km 3 . Glaciers in the basin play a significant role in the water resource system. It is estimated that they provide about 133 Â 10 8 m 3 of meltwater annually, contributing 39% of the total river runoff. Under the influence of global warming, northwest China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 1 publication
1
70
0
Order By: Relevance
“…This is in line with earlier studies which show that the highest glacier shrinkage occurred in the outer ranges of Tien Shan Mountains, or in peripheral, lower-elevation ranges near the densely populated forelands, while significantly smaller rates are reported for glaciers of inner ranges (Narama et al 2010, Sorg et al 2012. Typical published values for the outer ranges are loss rates of ∼0.6-0.7% per year in Northern and Western Tien Shan during 2000-2007(Narama et al 2010, ∼0.35% per year for Inner Tien Shan (Terskey Alatau, 1990-2003, Kutuzov and Shahgedanova 2009Akshiirak, 1977-2003, Aizen et al 2006) and 0.30-0.35% per year in Eastern Tien Shan (1963-2000, Liu et al 2006. A lower recession rate of 0.1% per year was found in the AksuRiver Basin in the Chinese part of the Central Tien Shan (1963( -2000( , Liu et al 2006.…”
Section: Glacier Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with earlier studies which show that the highest glacier shrinkage occurred in the outer ranges of Tien Shan Mountains, or in peripheral, lower-elevation ranges near the densely populated forelands, while significantly smaller rates are reported for glaciers of inner ranges (Narama et al 2010, Sorg et al 2012. Typical published values for the outer ranges are loss rates of ∼0.6-0.7% per year in Northern and Western Tien Shan during 2000-2007(Narama et al 2010, ∼0.35% per year for Inner Tien Shan (Terskey Alatau, 1990-2003, Kutuzov and Shahgedanova 2009Akshiirak, 1977-2003, Aizen et al 2006) and 0.30-0.35% per year in Eastern Tien Shan (1963-2000, Liu et al 2006. A lower recession rate of 0.1% per year was found in the AksuRiver Basin in the Chinese part of the Central Tien Shan (1963( -2000( , Liu et al 2006.…”
Section: Glacier Changesmentioning
confidence: 99%
“…Typical published values for the outer ranges are loss rates of ∼0.6-0.7% per year in Northern and Western Tien Shan during 2000-2007(Narama et al 2010, ∼0.35% per year for Inner Tien Shan (Terskey Alatau, 1990-2003, Kutuzov and Shahgedanova 2009Akshiirak, 1977-2003, Aizen et al 2006) and 0.30-0.35% per year in Eastern Tien Shan (1963-2000, Liu et al 2006. A lower recession rate of 0.1% per year was found in the AksuRiver Basin in the Chinese part of the Central Tien Shan (1963( -2000( , Liu et al 2006. Similarly, glaciers of the Akshiirak Range retreated by only 0.12% per year in an earlier period (1943( -1977( , Kuzmichenok 1989, while an acceleration of area loss was found during 1977-2003(Aizen et al 2006.…”
Section: Glacier Changesmentioning
confidence: 99%
“…Xinjiang is one of the most snowy and glaciated regions in China, and approximately 22,240 glaciers exist in the high-elevation mountains. These glaciers cover an area of 27,974 km 2 and store approximately 2,814.81 km 3 of ice [11,31]. The glaciers are mainly concentrated in the Tianshan and Kunlun Mountains, and glacier melt from these high mountains is a major water source for both humans and natural ecosystems in this region [32].…”
Section: Introductionmentioning
confidence: 99%
“…The glaciers are mainly concentrated in the Tianshan and Kunlun Mountains, and glacier melt from these high mountains is a major water source for both humans and natural ecosystems in this region [32]. Recent studies have suggested that glacial melting in the Tianshan Mountains is among the most rapid on Earth due to climate warming [30,31,33]. The resulting water might be an important resource for vegetation under a warming climate for the arid and semi-arid ecosystems near the mountains in Xinjiang.…”
Section: Introductionmentioning
confidence: 99%
“…There have been recent efforts to document the glacier area loss in different mountain regions (Li et al, 2008;Kang et al, 2010) or drainage basins (e.g., Liu et al, 2006;Shangguan et al, 2009) of western China, but none of these inventories has emphasized on the whole LRB. The Lancang River originates at the inland high Tibetan Plateau; flows through China to Myanmar, Laos, Thailand, Cambodia, and Vietnam; is here renamed the Mekong River; and then ultimately merges into the South China Sea.…”
Section: Introductionmentioning
confidence: 99%